1985
DOI: 10.1111/j.1365-2044.1985.tb11013.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of alfentanil, halothane and enflurane for day‐case gynaecological surgery

Abstract: SummarySixty patients received either alfentanil. halothane or enjlurane .for maintenance of anaesthesia during short day-case gynaecological procedures. The alfentanil group recovered more rapid1.v but there wus no difference between haloihane und enflurane in lerms of recovery time. Apnoea and movement during surgery only occurred in the patienis who received al/entanil. The incidence of other side effects was the same in each group, including late subjective feelings of drowsiness and unsteadiness Key words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Other authors have also found recovery with alfentanil to be more rapid than with halothane l3 • 15 or enflurane. 12 The results of the Trieger test, which was intended to demonstrate differences in the quality of recovery, were inconclusive. The Trieger test (a form of paper and pencil test) itself is a modification by Newman, Trieger and Miller, of Bender's Motor Gestalt test which was originally used in World War 11 to discover cases of abnormal cerebral function in Army Medical installations, 1 and later as an aid in diagnosis and psychotherapy in children with organic brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also found recovery with alfentanil to be more rapid than with halothane l3 • 15 or enflurane. 12 The results of the Trieger test, which was intended to demonstrate differences in the quality of recovery, were inconclusive. The Trieger test (a form of paper and pencil test) itself is a modification by Newman, Trieger and Miller, of Bender's Motor Gestalt test which was originally used in World War 11 to discover cases of abnormal cerebral function in Army Medical installations, 1 and later as an aid in diagnosis and psychotherapy in children with organic brain damage.…”
Section: Discussionmentioning
confidence: 99%